Impact of the COVID-19 pandemic on midwifery-led service provision in the United Kingdom in 2020-21: Findings of three national surveys. (September 2022) - Brigante, Lia; Morelli, Alessandra; Jokinen, Mervi; Plachcinski, Rachel; Rowe, Rachel
Highlights: These national surveys focused on changes to midwifery-led service provision during the Covid-19 pandemic in the UK and the Channel Islands in 2020-21. During the first wave of the pandemic (March-May 2020) in the UK and the Channel Islands, midwifery-led services were affected by closures, cancellations and re-organisation with evident centralisation towards hospital settings. During the second wave of the pandemic (January- February 2021) in the UK there was less disruption to midwifery-led services. However, there was still a significant impact on whether women could have a birth partner with them for early labour, during labour and in the immediate postnatal period. Abstract: Background: The COVID-19 pandemic required all healthcare systems to adapt quickly. There is some evidence about the impact of the pandemic on United Kingdom maternity services overall, but little is known about the impact on midwifery-led services, including midwifery units and home birth services. Objective: To describe changes to midwifery-led service provision in the United Kingdom and the Channel Islands during the COVID-19 pandemic. Design: Three national surveys were circulated using the United Kingdom Midwifery Study System (UKMidSS) and the Royal College of Midwives (RCM) Heads and Directors of Midwifery Network. The UKMidSS surveys took place in wave 1 (April to June 2020) and in wave 2 (February to March 2021). The RCM survey was conducted in April 2020. Findings: The response rate to the UKMidSS surveys was 84% in wave 1 and 70% in wave 2, while 48% of Heads and Directors of Midwifery responded to the RCM survey. Around 60% of midwifery units reported being open as usual in wave 1, with the remainder affected by closures. Fewer unit closures (15%) were reported in the wave 2 survey. Around 40% of services reported some reduction in home birth services in wave 1, compared with 15% in wave 2. The apparent impact of the pandemic varied widely across the four nations of the United Kingdom and within the English regions. Conclusions: The pandemic led to increased centralisation of maternity care and the disruption of midwifery-led services, especially in the first wave. Further research should focus on the reasons behind closures, the regional variation and the impact on maternity care experience and outcomes.